2022
DOI: 10.1002/joc.7508
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation–temperature relationships over Europe in CORDEX regional climate models

Abstract: We studied spatial and temporal patterns of precipitation-temperature (P-T) relationships through correlations between monthly standardized precipitation index (SPI) and monthly temperature anomalies in individual climatic seasons over Europe. In the observed data (represented by E-OBS), positive correlations (wet-warm/dry-cold relationships) prevail during winter over most of Europe, while negative values (dry-warm/wet-cold) are dominant in summer. In the next step, an ensemble of seven regional climate model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…It should be noted that precipitation observations are not assimilated into the ERA5 reanalysis but produced through large-scale cloud and precipitation schemes and parametrization of convection 19,42 . Therefore, uncertainties in the precipitation-temperature relationship 43 may affect the near-surface layers' temperature and heat wave 3D types, which will be addressed in further studies employing the E-OBS data set 44 for reference precipitation.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…It should be noted that precipitation observations are not assimilated into the ERA5 reanalysis but produced through large-scale cloud and precipitation schemes and parametrization of convection 19,42 . Therefore, uncertainties in the precipitation-temperature relationship 43 may affect the near-surface layers' temperature and heat wave 3D types, which will be addressed in further studies employing the E-OBS data set 44 for reference precipitation.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…A number of methods for estimation of PET were introduced but none of them outperforms others globally, as their performance is often linked to certain climatic region (Valipour et al., 2017). Some studies have reported that more complex radiation‐based models perform better under climate change conditions (Sheffield et al., 2012) but they demand variables (e.g., relative humidity, solar radiation, and wind speed) often laden with errors in RCMs (Lhotka & Kyselý, 2022b; Vautard et al., 2021), thus increasing uncertainties originating from climate models' selection. In addition, the limited requirements for input data in the Oudin's method allow evaluating the climate models against the established gridded observation‐based products (such as the E‐OBS data set; Cornes et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These variations between the sub-ensembles are linked to future changes in temperature, precipitation, and the mutual relationships between these two. Lhotka and Kyselý (2022b) showed that CORDEX RCMs have difficulties in reproducing links between summertime precipitation and temperature on the monthly scale and that these biases are RCM-dependent. In addition, differences between sub-ensembles are probably also linked to simulations of future changes in atmospheric circulation patterns (Zappa & Shepherd, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In F. adippe and F. niobe, melanisation increased with precipitation. We propose that because precipitation is often negatively correlated with temperature in European summers (Lhotka and Kyselý, 2022), exhibiting darker wings might be beneficial in areas with high precipitation. Together, these results strengthen the conclusion that the thermal milieu is a crucial selective driver for the degree of melanism in insects, and ectotherms generally.…”
Section: Large-scale Patterns Of Spatial Variation In Wing Size Were ...mentioning
confidence: 97%